Two new species of pilargid polychaetes (Annelida: Pilargidae) from the southern Gulf of California, Mexico - Cardona-Gutiérrez, María Fernanda; Tovar-Hernández, María Ana (Zootaxa, 2026)
Pilargids are annelid worms inhabiting soft-bottom sediments and are currently represented by 11 genera and approximately 100 described species worldwide. To date, 15 pilargid species have been originally described from Mexican waters. In the present study, two new species, Cabira mexicana sp. nov., and Litocorsa ambigua sp. nov., are described from shallow soft-bottoms of Laguna de La Paz, southern Gulf of California, Mexico, at depths ranging from 1.5 to 6.4 m. Comparative remarks with morphologically similar species are provided. Cabira mexicana sp. nov., is characterized by the presence of a unique set of features related to the first ventral cirri from chaetiger 3, first notopodial hooks from chaetiger 7, neurochaetae capillaries, non-limbate with entire tips, two small, rounded eyespots and pharynx with denticles. Litocorsa ambigua sp. nov., differs from all species mainly by the presence of furcate chaetae. Cabira mexicana sp. nov., and Litocorsa ambigua sp. nov., exhibit a patchy distribution within the lagoon, varying seasonally. Cabira mexicana sp. nov., was associated primarily with muddy to clay-rich sediments, whereas Litocorsa ambigua sp. nov., occurred in mud, clay, and silty sand substrates. Both species were recorded under marine salinities, well-oxygenated waters, and temperatures reflecting the seasonal variability of the lagoon. This study increases the known richness of Pilargidae in Mexican waters and highlights the importance of shallow coastal lagoons of the Gulf of California as reservoirs of little known annelid diversity.